2000
DOI: 10.1002/(sici)1097-4628(20000613)76:11<1644::aid-app5>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in Tencel by enzymatic hydrolysis

Abstract: ABSTRACT:The NaOH-, fibrillation-, and cellulase-treated Tencel fabrics were characterized by weight loss, tensile strength, scanning electron microscopy (SEM) analysis, X-ray diffraction analysis, measurements of moisture regain and dye adsorption (K/S value), degree of polymerization (DP), and copper number. Weight loss increased and tensile strength decreased with increase in cellulase concentration and treatment time. At a similar weight loss, tensile strength retentions of the NaOH-pretreated samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…No other new peak emerged, implying the low interaction between BaSO 4 particles and viscose matrix. reflection of cellulose II crystallite structure, respectively [17][18][19]. The diffraction peaks at 23.5 , 26.6 , 29.5 , 32.2 , and 43.7 were the characteristic peaks of orthorhombic BaSO 4 crystal, identical with that reported in the study by Ramaswamy et al [16].…”
Section: àsupporting
confidence: 87%
“…No other new peak emerged, implying the low interaction between BaSO 4 particles and viscose matrix. reflection of cellulose II crystallite structure, respectively [17][18][19]. The diffraction peaks at 23.5 , 26.6 , 29.5 , 32.2 , and 43.7 were the characteristic peaks of orthorhombic BaSO 4 crystal, identical with that reported in the study by Ramaswamy et al [16].…”
Section: àsupporting
confidence: 87%
“…In 1995, Pause managed to coat fibers with microencapsulated PCM (microPCM) and systematically studied the basic and dynamic thermal insulation of the fabrics using a range of different PCMs [4]. However, the surface coated fabrics became rougher and stiffer as the amount of microPCM increased, and thus the total hand value, which determines the tactile comfort perceived by humans, decreased [7]. Recently, Zhang et al successfully prepared thermo-regulating composite fibers by embedding the microPCM into the fibers via both melt-spinning [8] and wet-spinning [9] techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that pretreatments, especially soaking in sodium hydroxide, enhanced the cellulase production (Purwadaria et al 2004b). This result correlated with lignocellulose content that had been altered by sodium hydroxide where it breaks the lignin shield and disrupts the crystalline structure of cellulose (Shin et al 2000;Mosier et al 2005). Soaking pollard in water might reduce the reducing sugar availability in pollard or decrease the catabolite repression of enzymes.…”
mentioning
confidence: 88%